2021
DOI: 10.1002/eqe.3498
|View full text |Cite
|
Sign up to set email alerts
|

Free‐rocking tests of a freestanding object with variation of center of gravity

Abstract: Freestanding nonstructural objects are very common in various infrastructure systems, but their dynamic properties with variations in the center of gravity (CG) are not yet fully understood. To investigate the dynamic properties of a freestanding object as its CG is varied, a steel frame model was fabricated using movable steel plates. Two scenarios, with varying and fixed CG, were considered in the free rocking tests. The experimental rotation responses generally matched the analytical responses in the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 55 publications
(236 reference statements)
0
2
0
Order By: Relevance
“…As a very early study in this area, Housner [12] proposed a seminal framework to evaluate the seismic response of a solitary rigid block placed on a rigid base. Following this pioneering work, investigators over the world have endeavored to evaluate the rocking response of freestanding blocks, including experimental [13][14][15][16][17][18][19][20][21][22][23][24] and numerical approaches [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Early researchers have observed that a rocking motion has extremely complex dynamic characteristics and is barely "nonrepeatable" [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…As a very early study in this area, Housner [12] proposed a seminal framework to evaluate the seismic response of a solitary rigid block placed on a rigid base. Following this pioneering work, investigators over the world have endeavored to evaluate the rocking response of freestanding blocks, including experimental [13][14][15][16][17][18][19][20][21][22][23][24] and numerical approaches [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Early researchers have observed that a rocking motion has extremely complex dynamic characteristics and is barely "nonrepeatable" [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneering work, the seminal framework proposed by Housner [11] for the seismic response evaluation of freestanding rigid blocks has been followed by many in-vestigators, including experimental [12][13][14][15][16][17][18][19][20] and numerical efforts [21][22][23][24][25][26][27][28][29][30][31][32][33]. To predict the occurrence of overturning, Ishiyama [34] proposed overturning criteria involving the overturning acceleration and velocity, which are the minimum peak acceleration and velocity of the input excitation needed to overturn a rigid block, respectively.…”
Section: Introductionmentioning
confidence: 99%